AN INTERPERSONAL FUNCTION ANALYSIS OF JOKO WIDODO'S REMARKS IN G20 SESSION I - Desi Rahma Yuni Br.Sinulingga; Anna Theresia Simanjuntak; Nurlela Nurlela (XXXXXXXX, 2023)
This research investigates the interpersonal function in Indonesian president Joko Widodo’s remarks in G20 session I. The objective is to find out the mood, speech role and modality in Indonesian president Joko Widodo’s remarks in G20 session I. This research use qualitative descriptive research method. The data of this research are clauses from the text entitle "Remarks of President of the Republic of Indonesia in Session I of the G20 Summit on Global Economic Condition, Food Security, and Energy at the Apurva Kempinski Hotel, Nusa Dua in Bali Province November 15, 2022" By Office of Assistant to Deputy Cabinet Secretary for State Documents, published on November, 15th 2022. This research found three types of mood: Declarative mood, Imperative mood, and Interrogative mood, and the most dominant type is Declarative mood with percentage 80,43%. Then, this research also found three types of modality: Low, Median, and High, and the most dominant type is Median modality with percentage of 46,15%. Last, this research found four types of speech function: Statement, Question, Command, Offer, and the dominant types of speech function is statement with 78,72%.Keywords: Interpersonal function, mood types, modality types, speech function, remarks.